Bound to Respect : Antebellum Narratives of Black Imprisonment, Servitude, and Bondage, 1816-1861 - Green, Keith Michael, 1976- (Book collections on Project MUSE., 2015)
Winner of the Elizabeth Agee Prize in American Literature In Bound to Respect: Antebellum Narratives of Black Imprisonment, Servitude, and Bondage, 1816-1861, Keith Michael Green examines key texts that illuminate forms of black bondage and captivity that existed within and alongside slavery. In doing so, he restores to antebellum African American autobiographical writing the fascinating heterogeneity lost if the historical experiences of African Americans are attributed to slavery alone. The book's title is taken from the assertion by US Supreme Court chief justice Roger B. Taney in his 1857 Dred Scott decision that blacks had no rights that whites were "bound to respect." This allusion highlights Green's critical assertion that the dehumanizing absurdities to which defenders of slavery resorted to justify slavery only brought into more stark relief the humanity of African Americans. A gifted storyteller, Green examines four forms of captivity: incarceration, enslavement to Native Americans, child indentured servitude, and maritime capture. By illuminating this dense penumbra of captivity beyond the strict definitions of slavery, he presents a fluid and holistic network of images, vocabulary, narratives, and history. By demonstrating how these additional forms of confinement flourished in the era of slavery, Green shows how they persisted beyond emancipation, in such a way that freed slaves did not in fact partake of "freedom" as white Americans understood it. This gap in understanding continues to bedevil contemporary American society, and Green deftly draws persuasive connections between past and present. A vital and convincing offering to readers of literary criticism, African American studies, and American history, Green's Bound to Respect brings fresh and nuanced insights to this fundamental chapter in the American story.